Eco-efficient alkaline activated binders for manufacturing blocks and pedestrian pavers with low carbon footprint: Mechanical properties and LCA assessment - Mejía-Arcila, J.; Valencia-Saavedra, W.; Mejía de Gutiérrez, R. (Materiales de Construcción, 2020)
This study proposes using two types of binders based on fly ash (FA) as primary raw material and a calcium source such as ground granulated blast furnace slag (GBFS) or Portland cement (OPC) for the production of eco-efficient pre-fabricated materials. These binders are denoted FA/GBFS (70/30) and FA/OPC (80/20). A mix of commercial sodium silicate and sodium hydroxide was used as a traditional activator (SN), and the mix of rice husk ash (RHA) and NaOH as an alternative activator (RN). The results show the possibility of obtaining a binary cement (FA/GBFS-RN) with compressive strength up to 38 MPa after curing for 28 days and 65 MPa after curing for 360 days. The hybrid binder (FA/OPC-RN) reported 30 MPa and 61 MPa at the same age of curing. Additionally, FA/GBFS-RN reports reductions in the environmental and health impacts of up to 75% compared to systems made with sodium silicate and sodium hydroxide. Based on the results, FA/GBFS-RN paste was selected as the optimal material for producing masonry blocks and pedestrian pavers, which met the Colombian standards.